Seroprevalence for selected pathogens of zoonotic importance in wild nutria (Myocastor coypus) - Martino, Pablo Eduardo; Stanchi, Néstor Oscar; Silvestrini, María Pía; Brihuega, Bibiana Felicitas; Samartino, Luis Ernesto; Parrado, Eduardo Joaquín (Springer, 2019)
Little information is present in the literature on diseases of the nutria (Myocastor coypus) in the wild. Serum samples obtained from 176 trapped animals were tested for antibody reactivity against 11 pathogens of significant zoonoses. Sera were positive against Leptospira (38.0 %, odds relative risk = 0.03, Taylor series 95 % confidence limits 0.01–0.06), Toxoplasma gondii (27.8 %, odds relative risk = 2.30, Taylor series 95 % confidence limits 1.23–4.31), Chlamydophila psittaci (21.0 % odds relative risk = 4.94, Taylor series 95 % confidence limits 2.75–8.89), Streptococcus equi subspecies zooepidemicus (15.9 % odds relative risk = 1.87, Taylor series 95 % confidence limits 1.04–3.37), and encephalomyocarditis virus (3.4 %, odds relative risk = 0.05, Taylor series 95 % confidence limits 0.02–0.12). Some of the rodents showed antibodies at high titers, mostly indicating recent exposure. Seroprevalence rates varied among the location and age groups, although not by season or gender. All samples were seronegative for Brucella spp., Francisella tularensis, vesicular stomatitis virus, rabies virus, foot-and-mouth disease virus, and Encephalitozoon cuniculi.